FACIES LEGALIS OF THE END-OF-LIFE: A COMPARATIVE LAW PERSPECTIVE - HARRAR MASMOUDI, Wafa (MEDECINE LEGALE DROIT MEDICAL, 2025)
The topic of end-of-life is currently a major issue in many countries, giving rise to complex ethical, moral, and legal debates. The legal framework surrounding end-of-life practices varies from country to country, reflecting a lack of international consensus. Currently, there is no international consensus on the authorisation or prohibition of euthanasia, including active or passive euthanasia, or assisted suicide. The disagreement is understandable because of the difficulty in creating an objective text that justifies the decision to end a patient’s life, given the wide range of beliefs and cultural differences surrounding end-of-life practices worldwide.